Audiovisual resources to improve oral communication - Guayas Calva, Anthony Fabricio (Machala: Universidad Técnica de Machala, 2024)
This thesis focuses on improving oral communication in English through audiovisual resources, such as podcasts and videos. Following a quantitative perspective under an experimental design, the lack of communicative ability in English of the 28 students of the First Year of the Unified General Parallel Baccalaureate J of the Nueve de Octubre High School is addressed. Theoretical methods were used to substantiate the object of study, and empirical methods were used to obtain results that detail the student level. First, a pre-test was carried out to identify the level and skills that the students have to function in communication, and then a system of classes was carried out with the use of videos and podcasts to strengthen the weaknesses found in different English skills. Finally, a post-test was carried out to verify the process of improvement of the students' oral communication in English
Esta tesis se centra en mejorar la comunicación oral en inglés mediante recursos audiovisuales, siendo estos podcast y video. Siguiendo una perspectiva cuantitativa bajo un diseño experimental, se abordan la falta de habilidad comunicativa en inglés que tienen los 28 estudiantes del Primer Año de Bachillerato General Unificado paralelo J del Colegio de Bachillerato Nueve de Octubre. Se hizo uso de métodos teóricos para fundamentar el objeto de estudio, y métodos empíricos para obtener resultados que detallen el nivel estudiantil. Primeramente, hizo un pre-test para identificar el nivel y habilidades que tienen los estudiantes para desenvolverse en la comunicación, para después proceder a realizar un sistema de clases con el uso de videos y podcast para fortalecer las debilidades encontradas en distintas habilidades del inglés. Finalmente se realizó un post-test para verificar el proceso de mejoramiento de la comunicación oral en inglés de los estudiantes.
Keywords: RECURSO AUDIOVISUAL; SISTEMA DE CLASE; PODCAST; VIDEO